To solve this equation, we will first isolate the term with "x" on one side.
5/3 - 2x = 1/6
To move the term with "x" to the other side, we will subtract 5/3 from both sides:
-2x = 1/6 - 5/3
Next, we need to find a common denominator for 1/6 and 5/3, which is 6. We can rewrite 5/3 as 10/6:
-2x = 1/6 - 10/6
Now we can combine the fractions:
-2x = (1 - 10)/6
-2x = -9/6
Simplify the fraction:
-2x = -3/2
To solve for x, we will divide both sides by -2:
x = (-3/2) / (-2)
x = 3/4
Therefore, the solution is x = 3/4.
what is the solution of 5/3-2x=1/6
-11/12
3
3/4
-11/3
1 answer